Four hours of veno-venous extracorporeal membrane oxygenation using bi-caval cannulation affects kidney function and induces moderate lung damage in a mouse model - Natanov, Ruslan (Intensive Care Med Exp, 2019)
BACKGROUND: Improvement of single site cannulation for extracorporeal membrane oxygenation (ECMO) therapy is pivotal for reduction of patient morbidity and mortality in respiratory failure. To further improve the cardiopulmonary outcomes and reduce end organ damage, we established a murine model for single site cannulation with a double lumen cannula. RESULTS: We created a hemodynamically stable double lumen cannula and successfully implanted it through the jugular vein into the upper and lower vena cava. This allowed adequate drainage of the blood. Blood gas analysis showed excellent oxygenation and CO(2) reduction. There was no excessive bleeding. No signs of right heart congestion were present which was confirmed in the histological analysis of the liver. Histology demonstrated moderate lung damage and mild acute kidney injury. Neutrophil infiltration was similar in ECMO and sham kidneys. CONCLUSIONS: Veno-venous extracorporeal circulation deteriorates kidney function and promotes moderate pulmonary damage.